Kemandirian Pangan Sumber Karbohidrat dan Protein untuk Mewujudkan Ketahanan Pangan Keluarga - Rahmawati, Yulia; Nurani, Atat Siti; Sukandar, Dadang; Khomsan, Ali (INVOTEC, 2012)
This study aims to: formulate operational concepts to measure the level of household food endurance, to analyze indicators of household food endurance in terms of aspects of education, economics, and food consumption, identify the characteristics of households that experienced food unendurance. Household sample was pre-prosperous, prosperous I, prosperity II, prosperous III, and prosperous III +. Selection random sample coated with proportional allocation. Types of data collected include demographic characteristics of household, ownership of land, the economic characteristics of households, household social characteristics. Based on discriminant analysis, it found five variables that can be indicators of household food enduracnce is the wife of education backgaround, ownership of chickens, the frequency of eating rice consumption , cassava consumption frequency and the frequency of consumption of salted fish. The higher the wife's education, the more resistant the household food. While ownership of the chicken and salted fish consumption is indicated that is the opposite of more domesticated chickens and the higher the frequency of consumption of salted fish is the household food unendurance. Striking characteristic is the average frequency of consumption of salted fish, the frequency of household consumption of food endurance just 0.7 times per week, while the household does not endurance as much food frequency 3.9 times per week.